Relative Impact of Assistive Technology Diffusion: A Case Study from Abu Dhabi City Public Schools - AlMazrouei, Rashed Z (2021)
Thepurposeofthisstudyistoassess and investigate the relative contribu tion of assistive technology (AT)againstothersixintervention strategies. The student performance profile (SPP) was used as an instrument for the first time in the Middle East andintheUnitedArabEmirates(UAE).Thestudyappliedquantitativemethods andparametrictechniques,suchasOne-WayANOVA,FisherPairwiseComparisons, and paired t-tests, as well as descriptive and inferential statistics utilizing the data gathered during the research. This research was conducted at six public schools in AbuDhabiCity, covering 126 students with Special Education Needs and Disability (SEND)withvaryingdisabilitytypes.Studentswerefromgrades1–12andfromages 5–24. The student performance profile (SPP) was redesigned to suit the UAE educa tion system and schools. The data was then collected, studied, and analyzed using Minitab® 17. The analyzed data inferred that Assistive Technology, redesign the activity or adaptations of specific curricular tasks, and personal assistance interven tion strategies make similar high-level of contributions to help students with SEND to achieve individualized education program (IEP) objectives and goals among seven intervention strategies.